PENERAPAN MODEL TEAMS GAME TOURNAMENT (TGT) DAN EXPLICIT INSTRUCTION BERBANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR IPA - Juhata, Juhata; Halida, Halida; Aunurrahman, Aunurrahman (Jurnal Visi Ilmu Pendidikan, 2026)
This research is based on the fact that there are still some students who play around when the teacher explains the material, and the teacher explains without the help of various media and learning models in science subjects so that students feel bored and not enthusiastic about science lessons. The purpose of this study is to: 1) Science learning outcomes before using the Teams Game Tournament (TGT) model and explicit instruction assisted by snake and ladder media for students, 2) Science learning outcomes after using the Teams Game Tournament (TGT) model and explicit instruction assisted by snake and ladder media for students 3) Significant influence on the use of science learning outcomes before using the Teams Game Tournament (TGT) model and explicit instruction assisted by snake and ladder media for students on learning outcomes IPA. To achieve this goal, the researcher uses the Literature Review research method taken from various journals from Google Scholar. Based on the data analysis, it can be concluded that: 1) The learning outcomes of science before using the Teams Game Tournament (TGT) model and explicit instruction assisted by snake and ladder media for grade II students are not good, 2) The learning outcomes of multiplication material after using the Teams Game Tournament (TGT) model and explicit instruction assisted by snake and ladder media for grade II students are very good and 3) There is a significant influence on the use of the Teams Game Tournament (TGT) model and Explicit Instruction Assisted by Snake and Ladder Media on Science Learning Outcomes of Class II